Trend Perceraian Pasangan Lanjut Usia pada Masyarakat Muslim di Kabupaten Lampung Timur - Infiana Ahsani Rohimah; Husnul Fatarib; Isa Ansori; Nency Dela Oktora (Bulletin of Community Engagement, 2024)
The rise of divorce among the elderly, especially among Muslim communities in East Lampung Regency in recent years, is currently having an impact on increasing divorce rates in Indonesia. This research aims to understand the extent of the potential for divorce, and what are the causes behind divorce in the elderly, as well as what implications the parties receive after divorce. In its solution, this research uses a qualitative descriptive method. The results of this study show that the risk of divorce among the elderly is caused by ignoring problems that have occurred before, then driven by the desire to maintain a household that has existed for decades and tends to postpone divorce because it is a pity to end a relationship that has been established for a long time, also because of the existence of divorce. child. Apart from that, the causes of divorce that are often found are due to third parties, continuous fighting, lack of responsibility, family factors, economic factors, domestic violence, lack of communication, lack of fulfillment of inner income, and not the first marriage. The implications felt after divorce by the parties include disturbed psychological impacts, trauma, declining health, difficulty in establishing new relationships, and social impacts due to bad views from the surrounding environment.